2019
DOI: 10.1002/jbm.b.34320
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of novel platinum nanocomposite beads on oral squamous cell carcinoma cells

Abstract: Nanoparticles are used in industry and medicine, because of their physiochemical properties, such as size, charge, large surface area and surface reactivity. Recently, metal nanoparticles were reported to show cell toxicity on cancer cells. In this study, we focused novel platinum nanoparticles‐conjugated latex beads (P2VPs), platinum nanocomposite (PtNCP) beads, and investigated the possibility to incorporate novel anti‐cancer effect of these combined nanoparticles. Oral squamous cell carcinoma cell lines, HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In order to assess membrane integrity and cytotoxicity, U2OS cells were treated with PtNPs (10 μg/mL), DOX (1 μg/mL), CIS (5 μg/mL), or a combination of PtNPs (10 μg/mL) and DOX (1 μg/mL) or combination of DOX (1 μg/mL) and CIS (5 μg/mL) for 24 h. LDH assays revealed that U2OS cell cytotoxicity was remarkably higher in cells treated with a combination of PtNPs and DOX than in untreated cells or those treated with a single agent (Figure 6A). Similarly, Tanaka et al [47] found that HSC-3-M3 cells treated with PtNCP beads at concentrations above 50 μg/mL exhibited greater LDH leakage than untreated cells and demonstrated increased extracellular LDH levels depending on the concentration of PtNCP beads. To further confirm the effect of PtNPs on membrane integrity and their cytotoxic effects against U2OS cells, PtNPs (10 μg/mL), DOX (1 μg/mL), or a combination of PtNPs (10 μg/mL) and DOX (1 μg/mL) or combination of CIS (5.0 μg/mL) and DOX (1 μg/mL) were incubated with the cells for 24 h and a trypan blue dye exclusion assay was performed.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In order to assess membrane integrity and cytotoxicity, U2OS cells were treated with PtNPs (10 μg/mL), DOX (1 μg/mL), CIS (5 μg/mL), or a combination of PtNPs (10 μg/mL) and DOX (1 μg/mL) or combination of DOX (1 μg/mL) and CIS (5 μg/mL) for 24 h. LDH assays revealed that U2OS cell cytotoxicity was remarkably higher in cells treated with a combination of PtNPs and DOX than in untreated cells or those treated with a single agent (Figure 6A). Similarly, Tanaka et al [47] found that HSC-3-M3 cells treated with PtNCP beads at concentrations above 50 μg/mL exhibited greater LDH leakage than untreated cells and demonstrated increased extracellular LDH levels depending on the concentration of PtNCP beads. To further confirm the effect of PtNPs on membrane integrity and their cytotoxic effects against U2OS cells, PtNPs (10 μg/mL), DOX (1 μg/mL), or a combination of PtNPs (10 μg/mL) and DOX (1 μg/mL) or combination of CIS (5.0 μg/mL) and DOX (1 μg/mL) were incubated with the cells for 24 h and a trypan blue dye exclusion assay was performed.…”
Section: Resultsmentioning
confidence: 86%
“…Kumari et al [45] reported that the combination of curcumin loaded selenium NPs (Se-CurNPs) and DOX and CD44-targeted DOX-loaded NPs (PSHA-DOXNPs) remarkably reduced HCT116 cell proliferation. Similarly, PtNPs were shown to dose-dependently inhibit the proliferation of human monocytic THP-1 and prostate cancer (LNCaP) cells [46], whilst Pt nanocomposite (PtNCP) beads reduced the viability of oral squamous cell carcinoma (HSC-3-M3) cells [47]. GOPtNPs significantly reduced cell viability and increased apoptosis in Colo 205 and HepG2 cells; however, no significant effects was observed in HT-29, HTC-116, SW480, MCF-7, LNCaP, or Hela B cells [48].…”
Section: Resultsmentioning
confidence: 99%
“…The results depicted that treatment with PtNCP beads suppressed tumor growth and identified increasing pathological necrotic areas. In vitro data suggest that PtNCP beads inhibited cell viability of HSC-3-M3 cells in a dose-dependent manner and induced cytotoxicity with increased leakage of lactate dehydrogenase [220]. Recently, Gurunathan et al [101] reported that apigenin functionalized PtNPs exhibited potential cytotoxicity, genotoxicity, and proinflammatory responses in human monocytic cell line (THP-1) by increasing the levels of lactate dehydrogenase, generation of ROS, and production of malondialdehyde, nitric oxide, and carbonylated proteins and also increased apoptosis and oxidative DNA damage.…”
Section: Cytotoxicity Of Ptnps In Cancer and Non-cancer Cellsmentioning
confidence: 98%
“…A wide variety of NPs were proven to be effective against a number of oral cancer cell lines, including human Caucasian dysplastic oral keratinocytes (DOK) [ 205 , 207 ], mouth epidermoid carcinoma (KB) [ 203 , 208 , 209 , 210 , 211 , 212 ], murine AT-84 oral squamous carcinoma cells [ 213 ], oral squamous cancer cell lines of Asian origin (ORL-48 and ORL-115) [ 214 ], human oral squamous cell carcinoma lines (PE/CA-PJ15 [ 215 ], OEC-M1 [ 216 ], HSC2 [ 217 ], YD-9 [ 218 ], SAS [ 219 , 220 ], HSC4 [ 1 , 220 ], KOSC [ 220 ], HSC3 [ 204 , 221 , 222 ], HSC-3-M3 [ 7 ], Ca9-22 [ 223 ], CAL 27 [ 222 , 223 , 224 , 225 , 226 , 227 ], SCC131 [ 228 ], SCC4 [ 222 , 228 ], VB6 [ 229 ], and H357 [ 229 , 230 , 231 ]), human tongue carcinoma cell lines (SCC-9 [ 232 , 233 , 234 ], SCC-25 [ 224 , 230 , 233 , 235 ], SCC-15 […”
Section: Head Neck and Oral Cancermentioning
confidence: 99%
“…One of the main challenges for dental researchers is to develop materials that can withstand the harsh conditions of the oral environment while remaining biologically sustainable and biocompatible [4,5]. NPs are gaining momentum in dentistry due to their physicochemical and biological properties, including biocompatibility, size, charge, large surface area, strength, solubility, chemical and surface reactivity, color, high stability, and thermal conductivity [6][7][8]. Such properties have allowed the development of new, innovative materials and the expansion and improvement of their functions [9].…”
Section: Introductionmentioning
confidence: 99%